Measuring the impact of blockchain and smart contracts on construction supply chain visibility. (October 2021) - Hamledari, Hesam; Fischer, Martin
Highlights: Assessing the visibility benefits of blockchain via comparative empirical experiments. Blockchain solutions outperform conventional ones at high information granularities. Blockchain and smart contracts enhanced the completeness and accuracy of information. At the lowest granularity, blockchain provided no benefits over state of practice. blockchain solution more robust than conventional one in maintaining visibility. Abstract: This work assesses the impact of blockchain and smart contracts on the visibility of construction supply chain and in the context of payments (intersection of cash and product flows). It uses comparative empirical experiments (Charrette Test Method) to draw comparisons between the visibility of state-of-practice and blockchain-enabled payment systems in a commercial construction project. Comparisons were drawn across four levels of granularity. The findings are threefold: 1) blockchain improved information completeness and information accuracy compared with the digital state-of-practice solution; 2) the improvements were significantly more pronounced for information queries that had higher product, trade, and temporal granularity; and 3) blockchain-enabled solution was robust when faced with more granular information queries, while the conventional solution experienced 50% and 66.7% decline respectively in completeness and accuracy of information. The paper concludes with a discussion of mechanisms contributing to visibility and the implications for the construction industry.